A geometric theory for 2-D systems including notions of stabilisability - Ntogramatzidis, Lorenzo; Cantoni, M.; Yang, R. (Springer Netherlands, 2008)
In this paper we consider the problem of internally and externally stabilising controlled invariant and output-nulling subspaces for two-dimensional (2-D) Fornasini–Marchesini models, via static feedback. A numerically tractable procedure for computing a stabilising feedback matrix is developed via linear matrix inequality techniques. This is subsequently applied to solve, for the first time, various 2-D disturbance decoupling problems subject to a closed-loop stability constraint.